2021
DOI: 10.1155/2021/6647107
|View full text |Cite
|
Sign up to set email alerts
|

Acetylshikonin Induces Apoptosis in Human Colorectal Cancer HCT‐15 and LoVo Cells via Nuclear Translocation of FOXO3 and ROS Level Elevation

Abstract: Acetylshikonin, a naphthoquinone, is a pigment compound derived from Arnebia sp., which is known for its anti-inflammatory potential. However, its anticarcinogenic effect has not been well investigated. Thus, in this study, we focused on investigating its apoptotic effects against HCT-15 and LoVo cells, which are human colorectal cancer cells. MTT assay, cell counting assay, and colony formation assay have shown acetylshikonin treatment induced cytotoxic and antiproliferative effects against colorectal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Previous studies represented to present that overexpression of HGF/cMet inhibited apoptosis in cancer cells via modulating mitochondrial proteins [40]. ROS-mediated apoptosis is critically associated with the intracellular ROS accumulation and regulation of the proapoptotic BH3-only proteins (Bim and Bax) and anti-apoptotic proteins (Bcl-xL) expression, which triggers mitochondrial membrane permeabilization [41,42]. Thus, we verified that transfection of Crispr-HGF and H2O2 induced apoptosis in HCC Huh7 and Hep3B cells.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies represented to present that overexpression of HGF/cMet inhibited apoptosis in cancer cells via modulating mitochondrial proteins [40]. ROS-mediated apoptosis is critically associated with the intracellular ROS accumulation and regulation of the proapoptotic BH3-only proteins (Bim and Bax) and anti-apoptotic proteins (Bcl-xL) expression, which triggers mitochondrial membrane permeabilization [41,42]. Thus, we verified that transfection of Crispr-HGF and H2O2 induced apoptosis in HCC Huh7 and Hep3B cells.…”
Section: Discussionsupporting
confidence: 71%
“…Primary antibodies were diluted to 1 : 500~1000 ratio, and secondary antibodies were diluted to 1 : 5000 ratio for use. All the experimental protocols were referred from our previous publications [ 13 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, acetylshikonin was assessed as an alternative and the result was pleasable that acetylshikonin had much less toxicity than shikonin in normal cells with corresponding antigenotoxic effect [ 12 ]. Furthermore, our previous study demonstrated that cytotoxicity was negligible in normal cells up to 5 μ M of concentration [ 13 ]. The anticancer effects of acetylshikonin is emerging in various cancer cells [ 14 ] and identified as the novel CYP2J2 inhibitor in hepatocellular carcinoma HepG2 cells [ 15 ], but the effects in RCC were not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…ASH induces apoptosis in a wide range of tumor cells, such as ROS-dependent apoptosis in oral squamous cell carcinoma cells (Ca9-22) [7]. Recent investigations have shown that ASH increases ROS and nuclear damage with subsequent nuclear translocation of FOXO3 and induced caspase-dependent apoptosis in osteosarcoma U2OS, renal cell carcinoma and colorectal cancer HCT-15, and LoVo cells [85][86][87]. It has also been reported that ASH induces dose-dependent apoptosis via activation of caspase-3/-7 and -9 in chondrosarcoma cell lines [88].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that an increase of pro-apoptotic Bcl2 family proteins or decrease in anti-apoptotic Bcl2 protein expression might be involved in mitochondrial damage, increase in cellular ROS and decrease in mitochondrial membrane potential [31,46,49,70,[91][92][93]. It has been showed that ASH induces apoptosis in osteosarcoma U2OS cells , A498 and ACHN (human RCC cell lines), colorectal Cancer HCT-15 and LoVo cells, and human leukemia cell line K562, via changing the Bcl2 family proteins [85][86][87]89]. Interestingly, our investigations showed that ASH did not significantly change Bax, Bcl2, Bcl-XL and Mcl-1 expression while it decreased mitochondrial membrane potential, increased ROS, activated caspase-3/-7 and induced apoptosis in GBM cell lines (U87 and U251).…”
Section: Discussionmentioning
confidence: 99%